1996
DOI: 10.1177/095632029600700405
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HCMV Activity of Cidofovir in Combination with Antiviral Compounds and Immunosuppressive Agents: In-Vitro Analyses

Abstract: SummaryCidofovir 1-[(S)-3-hydroxy-2-(phosphonomethoxy) propyl] cytosine, HPMPC] is an acyclic cytosine nucleotide analogue with potent in-vitro and in-vivo activity against a broad spectrum of herpesviruses including human cytomegalovirus (HCMV). Cidofovir has recently been shown to delay the progression of HCMV retinitis in AIDS patients. Therefore, the effects of several antiviral compounds (GCV, AZT, ddC, ddl, d4T, 3TC and PMEA) on the anti-HCMV activity of cldofovir were investigated in vitro. Cidofovir in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Furthermore, none of the combinations showed increased cytotoxicity in comparison with each drug alone. 28 Snoeck et al have demonstrated that cidofovir in combination with ganciclovir, AZT, foscarnet, or acyclovir showed additive to synergistic inhibition of HCMV replication in vitro. 29 Additionally, antiviral activity of cidofovir was determined in the presence of several immunosuppressive agents (hydrocortisone, cyclosporine A, methotrexate and mycophenolic acid) that are commonly used in the management of organ transplantation rejection in the transplant patients.…”
Section: Cidofovir: Mechanism Of Action and In Vitro Activitymentioning
confidence: 98%
“…Furthermore, none of the combinations showed increased cytotoxicity in comparison with each drug alone. 28 Snoeck et al have demonstrated that cidofovir in combination with ganciclovir, AZT, foscarnet, or acyclovir showed additive to synergistic inhibition of HCMV replication in vitro. 29 Additionally, antiviral activity of cidofovir was determined in the presence of several immunosuppressive agents (hydrocortisone, cyclosporine A, methotrexate and mycophenolic acid) that are commonly used in the management of organ transplantation rejection in the transplant patients.…”
Section: Cidofovir: Mechanism Of Action and In Vitro Activitymentioning
confidence: 98%